Kerja-Kerja Buah Roh dalam Pembelajaran Karakter Siswa Sekolah Dasar Palangka Raya - Depi Triani; Mika Melliani; Restiani, Restiani (Jurnal Multidisiplin Indonesia, 2024)
The objective of this study is to ascertain the impact of integrating the values of the Fruit of the Spirit into the curriculum for first-grade elementary school students. The methodology employed is a qualitative approach with a classroom action research design. The research sample consisted of 10 first-grade students at SD Negeri 12 Palangkaraya. The instruments used were observations and interviews with teachers and students. The results of the research indicate that the application of the values of the Fruit of the Spirit, including love, joy, and kindness, can lead to an increase in students' positive behavior within the classroom setting. Therefore, it can be concluded that the implementation of the values of the Fruit of the Spirit can serve as an effective strategy for the formation of children's character at the elementary school level.